Public knowledge, beliefs, psychological responses, and behavioural changes during the outbreak of COVID-19 in the Middle East - Husam Abazid; Iman A. Basheti; Esraa E. Al-Jomaa; Ayham Abazid; Warda M. Kloub (Centro de Investigaciones y Publicaciones Farmaceuticas, 2021)
Objective: To evaluate the knowledge, believes, psychological and behavioural impact of COVID-19 on the general population in the Middle East, exploring how it impacted public lives. Methods: A descriptive cross-sectional online survey was sent to a convenience sample in the Middle East through social media (Facebook and WhatsApp) between 16th of June and 30th of June 2020. The questionnaire was designed to collect the demographic, participant's source of information regarding COVID-19, knowledge and believes about COVID-19, the psychological consequences of COVID-19, impact of COVID-19 on participant's behaviour. The final version of the questionnaire was further tested for content validity by experts in the field. Results: A total of 2,061 participants completed the survey, with the majority being females (n=1394, 67.6%), from urban areas (n=1896, 92%) and the majority were from countries of The Levant (n=1199, 58.1%), followed by the Arabian Peninsula (n=392, 19.1%), Iraq (n=300, 14.6%) and Egypt (n=138, 6.7%). Few participants (3.0%) reported to have been infected and many (n=1847, 89.6%) were committed to quarantine at home. Social media platforms were the most common sources of information (41.2%). Many (63%) believed that COVID-19 is a biological weapon and were afraid of visiting crowded places (85%). The majority avoided public facilities (86.9%) such as prayer places and believed that the news about COVID-19 made them anxious (49.5%).